ANALISIS SISTEM ANTRIAN PADA KASIR DI BUMI NYIUR SWALAYAN PUSAT DI KOTA PALU - Asmirani, Asmirani (JURNAL ILMU MANAJEMEN UNIVERSITAS TADULAKO, 2017)
The purpose of this study was to determine whether the queuing system at the cashier that was implemented in the Bumi Nyiur Swalayan Center expenditure center had been effective or not. This study uses the M / M / S model queue formula. The conclusion of this study shows that the queuing system at Bumi Nyiur Swalayan Center Palu City using 4 cashiers, has an average percentage of ? value of 57.18% which is in the ineffective category. The most effective number of cashiers is 3 cashiers that have an average value of ? of 76.23%, which can be used in quite effective categories, but with consideration there is an increase in the number of employees serving in the cashier.